2020
DOI: 10.1111/hdi.12822
|View full text |Cite
|
Sign up to set email alerts
|

Low body cell mass index in hemodialysis patients: Association with clinical parameters and survival

Abstract: Introduction: Body cell mass (BCM) is a useful nutritional marker and is not affected by changes in the hydration status that commonly occur in hemodialysis (HD) patients. This study aimed to examine the association between body cell mass index (BCMI) and nutritional parameters, as well as its relationship with long-term survival in these patients.Methods: This longitudinal prospective multicenter study followed a cohort of patients in HD for 24 months. The clinical parameters of 2527 patients (mean age 70.3 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Evidence suggested that serum albumin can combine with amyloid-β and can reduce its neurotoxicity by inhibiting its aggregation and fibrosis, thus preventing further progression of cognitive decline ( Stanyon and Viles, 2012 ). Meanwhile, it is reported that BMI has an effect on energy metabolism through regulating body cell mass, which is one of the key factors to reflect nutritional status ( Oliveira et al, 2020 ). According to previous studies, overweight old people were found to have a lower risk of cognitive impairment or dementia compared with under or normal weight ( Hou et al, 2019 ; Li et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggested that serum albumin can combine with amyloid-β and can reduce its neurotoxicity by inhibiting its aggregation and fibrosis, thus preventing further progression of cognitive decline ( Stanyon and Viles, 2012 ). Meanwhile, it is reported that BMI has an effect on energy metabolism through regulating body cell mass, which is one of the key factors to reflect nutritional status ( Oliveira et al, 2020 ). According to previous studies, overweight old people were found to have a lower risk of cognitive impairment or dementia compared with under or normal weight ( Hou et al, 2019 ; Li et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…BCM is an important indicator in the analysis of human body composition; it is de ned as the total mass of metabolically active, viable, functional cells [40] . Increasing evidence shows that BCM is closely related to the in ammatory response in cancer patients, elderly patients, patients with chronic diseases, and hemodialysis patients, and it has an impact on patients' clinical outcomes [41][42][43][44] . Toshimi [45] et al con rmed that low preoperative BCM (BCM ≤ 23 kg) was a risk factor for sepsis and death from infection after liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the speci city of these indicators is not high [23][24][25][26] , and most studies are based on a one-time cutoff point and lack observations of dynamic change trends; thus, the predictive performance of these indicators is controversial, and they are not suitable as early and effective prognostic indicators for neurocritical patients. In recent years, studies have con rmed that relevant indicators measured by bioelectrical impedance analysis (BIA), such as phase angle (PA), BCM, and hydration status, are associated with in ammatory responses and a poor prognosis in patients who are elderly, have cancer, are undergoing hemodialysis, or are critically ill [27][28][29][30][31] . They are expected to become novel indicators for predicting patient prognosis, but their predictive e cacy needs to be further veri ed.…”
Section: Introductionmentioning
confidence: 99%
“…Both LTI and BCMI are associated with resting energy expenditure. 36,37 In terms of theory, BCMI reflects the most metabolically active part of fat-free mass, which is not affected by hydration status, and should perform better than LTI. Our results show that BCMI performed similarly to LTI.…”
Section: Discussionmentioning
confidence: 99%